SIKAP PETANI WORTEL TERHADAP KEBERADAAN SUB TERMINAL AGRIBISNIS (STA) WATUSAMBANG DI KECAMATAN TAWANGMANGU, KABUPATEN KARANGANYAR - Annisaa Dwi Prihatin; Eny Lestari; Hanifah Ihsaniyati (AGRITEXTS: Journal of Agricultural Extension, 2018)
This research are to analyze the farmers’s attitude to the existence of the STA   Watusambang,   analyze   the   factors   forming   attitudes,   and   analyze   the relationships between the factors forming attitudes and the farmers’s attitude to the existence  of  STA  Watusambang.  The  basic  method  used  in  this  research  was descriptive quantitative with survey technique. The location of the research was determined purposively in Blumbang Village, Tawangmangu Subdistrict, Karanganyar Regency. Sampling method used proportional random sampling, there were 60 carrot farmers chosen from each member farmer groups (4 farmer groups). The attitude- forming  of  carrot  farmers  in  this  research  is  age,  formal  education,  personal experience, culture, and exposure to the mass media. The relationship of attitude- forming factors with the farmers’s attitude could be known by using Rank Spearman analysis. The result of this research indicate that the attitude of carrot farmers against to  STA  Watusambang  50.0%  as  much  as  the  farmer  respondents  have  a  neutral attitude. The largest percentage age farmer respondents in the age category 37-44 years, formal education and culture in low category, personal experience and influence others who are considered important in the medium category, and exposure to the mass media in the category. Relationship analysis of test results showed there are a very significant relationship (α=0,01) between the influence of others considered important, personal experiences, and culture with an attitude of carrot farmers against STA; There is no significant relationship between age, formal education, and the media with the attitude of carrot farmers against the STA.